2022
DOI: 10.3390/curroncol29020091
|View full text |Cite
|
Sign up to set email alerts
|

CT and 3 Tesla MRI in the TN Staging of Colon Cancer: A Prospective, Blind Study

Abstract: (1) Background: Computer tomography (CT) scanning is currently the standard method for staging of colon cancer; however, the CT based preoperative local staging is far from optimal. The purpose of this study was to investigate the sensitivity and specificity of magnetic resonance imaging (MRI) compared to CT in the T- and N-staging of colon cancer. (2) Methods: Patients underwent a standard contrast-enhanced CT examination. For the abdominal MRI scan, a 3 Tesla unit was used, including diffusion weighted imagi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 34 publications
(55 reference statements)
0
7
0
Order By: Relevance
“…In addition, the level of movement disruption of the presence of water at the cellular level correlates with tumor aggressiveness (37) and is different between original tumorous and metastatic tissue. The recently published study provided by Rafaelsen et al (5) has shown that the diffusion restriction was significantly lower in mucin-containing colonic tumors, where the mean primary tumor ADC values tended to be lower in patients with distant metastases than in those without it. Though the data in our study relate to non–mucinous adenocarcinomas, differences in the amount of the mucin component (range = 0%–50%) (38), is a possible clue for unexpected findings related to the tumor grade.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In addition, the level of movement disruption of the presence of water at the cellular level correlates with tumor aggressiveness (37) and is different between original tumorous and metastatic tissue. The recently published study provided by Rafaelsen et al (5) has shown that the diffusion restriction was significantly lower in mucin-containing colonic tumors, where the mean primary tumor ADC values tended to be lower in patients with distant metastases than in those without it. Though the data in our study relate to non–mucinous adenocarcinomas, differences in the amount of the mucin component (range = 0%–50%) (38), is a possible clue for unexpected findings related to the tumor grade.…”
Section: Discussionmentioning
confidence: 93%
“…As the fourth most common form of cancer occurring worldwide, colorectal carcinoma is a central issue requiring better diagnostic and therapeutic options (1,2). Though neoadjuvant chemotherapy (NAC) for rectal cancer has been well established (3), there is still ongoing research in the use of NAC in the setting of colonic cancer (4,5). Several recent studies have shown promising results using NAC in colon cancer before surgery (6)(7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…The small number of participants might reduce the credibility and stability of the results. Moreover, the small sample sizes also limited further subgroup analyses or sensitivity analyses, e.g., only a few studies on colon cancer were available, and MRI with DWI was reported to have a better performance in detecting more colonic cancers than CT ( 36 ). Second, some of the studies did not match the participants by age or gender.…”
Section: Discussionmentioning
confidence: 99%
“…Magnetic resonance imaging had significantly higher sensitivity than CT scan in identifying T3 tumors (80% vs 51%). 77 In contrast, Hunter et al prospectively analyzed the accuracy of CT and MRI in 53 patients with T3 colon cancer and reported no significant differences in accuracy. 75 In other studies, CT has accurately identified high-risk colon cancer, with low rates of over-staging.…”
Section: Management Controversiesmentioning
confidence: 99%
“…[72][73][74] Various studies have been conducted to evaluate the staging accuracy of MRI, as it offers better soft tissue contrast. [75][76][77][78] A retrospective analysis in 2019 by Fernandez et al focused on 150 patients who underwent right colectomy between 2011 and 2016 at two institutions, with the goal of evaluating accuracy of CT staging for proximal colon cancer. The authors found CT failed to recognize the primary cancer in 18% of cases and over-staged tumor and lymph node involvement in 23.7% and 28.7% of cases, respectively.…”
Section: Role Of Ct Scan For Initial Stagingmentioning
confidence: 99%